2013
DOI: 10.1021/nn304064u
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Impact of Catalyst Phase Transition on Carbon Nanotube Growth byin SituRaman Spectroscopy

Abstract: The physical state of the catalyst and its impact on the growth of single-walled carbon nanotubes (SWNTs) is the subject of a long-standing debate. We addressed it here using in situ Raman spectroscopy to measure Fe and Ni catalyst lifetimes during the growth of individual SWNTs across a wide range of temperatures (500-1400 °C). The temperature dependence of the Fe catalyst lifetimes underwent a sharp increase around 1100 °C due to a solid-to-liquid phase transition. By comparing experimental results with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 39 publications
(60 reference statements)
1
48
0
Order By: Relevance
“…SWCNT growth from solid catalysts has been confirmed as well as nanowire growth [22,23]. The active forms of Fe catalyst have been reported to be liquid phase, solid Fe metal or Fe carbide depending on the growth temperature and the carbon contamination level [22,24,25]. The Ni catalyst is reported to be in the solid state up to 1200 °C [24].…”
Section: Swcnt Growth Mechanism From Gold Nanoparticlesmentioning
confidence: 87%
See 1 more Smart Citation
“…SWCNT growth from solid catalysts has been confirmed as well as nanowire growth [22,23]. The active forms of Fe catalyst have been reported to be liquid phase, solid Fe metal or Fe carbide depending on the growth temperature and the carbon contamination level [22,24,25]. The Ni catalyst is reported to be in the solid state up to 1200 °C [24].…”
Section: Swcnt Growth Mechanism From Gold Nanoparticlesmentioning
confidence: 87%
“…The active forms of Fe catalyst have been reported to be liquid phase, solid Fe metal or Fe carbide depending on the growth temperature and the carbon contamination level [22,24,25]. The Ni catalyst is reported to be in the solid state up to 1200 °C [24]. The point is that carbon uptake into the metal particles and carbon precipitation from the carbon-metal eutectic alloy, i.e., continuous carbon supply from the bulk of the nanoparticle.…”
Section: Swcnt Growth Mechanism From Gold Nanoparticlesmentioning
confidence: 99%
“…[8] The recent in-situ Raman analyses also revealed that CNTs could grow from both solid and liquid catalyst Fe, depending on the growth temperature. [9] The debate on the chemical state of catalysts was originated from the argument in 1980s that the deviation of C equilibrium during the growth process of CNFs could be attributed to the formation of the metastable carbides, Ni 3 C or Ni 3 C 1-x . [7,[10][11][12] However, the validity of such a carbide-assisted mechanism has been strongly questioned in the past.…”
Section: Introductionmentioning
confidence: 99%
“…Raman 4 modes provide fingerprints of carbon to track the thermodynamics and kinetics of in-situ carbon growth processes, such as for single-walled carbon nanotubes and graphene. [25][26][27] In-situ monitoring enables the capability to finely distinguish between mechanistic processes occurring in the growth of carbon nanostructures.…”
Section: Introductionmentioning
confidence: 99%